Designing of Zinc Oxide/Zinc Sulfide Heterojunction Arrays as Potential Semiconductors for Promoting Safe Energy Storage in Eco‐Friendly Batteries - Mollaamin, Fatemeh; Monajjemi, Majid (Wiley, 2025)
ABSTRACTThe first principles calculations were applied to investigate the structural stability and electronic properties of cubic zinc oxide (ZnO) and cubic zinc sulfide (ZnS) heterostructures adsorbed with H2O molecules. A comprehensive investigation on H2O grabbing by ZnO/ZnS heterostructures was carried out using DFT computations at the CAM–B3LYP–D3/6–311 + G (d, p) level of theory. The hypothesis of the energy adsorption phenomenon was confirmed by density distributions extracted from CDD, TDOS/PDOS/OPDOS, and LOL parameters for ZnO/ZnO–H2O or ZnS/ZnS–H2O. A vaster jointed area engaged by an isosurface map for H/OH adsorption on ZnO or ZnS surface toward the formation of ZnO–H2O or ZnS–H2O complex due to labeling atoms of O1, Zn15, O27, or S27, H29, H30. Therefore, it can be considered that zinc in the functionalized ZnO or ZnS might have more impressive sensitivity for accepting the electrons in the process of H/OH adsorption. It is considerable that when all surface atoms of ZnO or ZnS are coated by OH and H groups, the semiconducting behavior is recovered. Depending on the stability of the heterostructures, H2O exhibits both chemisorption and dissociation on the surfaces of the heterostructures. Finally, it was observed that the prepared nano semiconductors exhibit significant activity through H(OH) adsorption. The enhanced semiconducting activity of ZnO or ZnS can be attributed to the slower recombination of the electron–hole pairs in this semiconductor material. The reactive species OH•, •O2−, and H+ are believed to play important roles in the semiconductor devices.